A Study of Correlation among Undergraduate Students’ Learning Styles, Intensity of Watching YouTube Videos and Listening Proficiency in the ELT Context - Nayyer Hassan; Haider, Muzmmal; Aleem, Faiza (JCTE, 2026)
The current study investigates the correlation between students’ learning styles, the amount of time spent watching YouTube videos, and their current listening proficiency level. The study’s population was undergraduate students from private universities in Pakistan. The researcher employed a quantitative and correlational method to fulfil the study’s objective. Students’ learning styles were examined using the VAK Learning Style Inventory developed by Chislett and Chapman (2005). An IELTS listening sample test was used to investigate students’ listening proficiency levels. To gain more insight into students’ practice of watching YouTube videos, a quantitative questionnaire (Likert Scale) consisting of five questions was distributed among the students. A sample of a hundred students was randomly selected to collect data. The results depict a positive correlation between students’ intensity of watching YouTube videos and their listening proficiency level. However, there is a negative correlation between the learning styles of students and their intensity of watching YouTube videos, with an insignificant p-value. The study reveals that students’ learning styles do not significantly contribute to motivating them to watch YouTube videos. The study recommends further investigation using different variables, such as students' self-directed learning habits, the influence of guided YouTube usage, motivation, and access to technology.